Shared decision making in dysphagia. (7th July 2022) - Atkinson, Katie
Abstract : The term 'risk feeding' usually applies where a person continues to eat and drink despite aspiration. This term has been increasingly challenged. Risk feeding has connotations of risk-taking behaviour and may conflict with healthcare values of keeping people safe. 'Risk' is difficult to quantify in dysphagia and interventions to reduce risk are not risk-free. The relationship between aspiration and pneumonia is complex, as are the success of the interventions designed to prevent them. Attempts to eliminate risk may lead to heavy restriction with unsatisfactory evidence, at a cost to quality of life. The Royal College of Speech and Language Therapists (RCSLT) has introduced a framework for multidisciplinary, person-centered decision making: Eating and Drinking with Acknowledged Risk . Every decision we make carries risk and as humans we balance these based on our personal values and goals. This is supported by the Mental Capacity Act 2005 and it is our role to achieve this for our patients. This article discusses these complexities and describes the RCSLT framework, with particular focus on the role of the nurse.